2022
DOI: 10.1186/s12866-022-02671-2
|View full text |Cite
|
Sign up to set email alerts
|

The electronic tree of life (eToL): a net of long probes to characterize the microbiome from RNA-seq data

Abstract: Background Microbiome analysis generally requires PCR-based or metagenomic shotgun sequencing, sophisticated programs, and large volumes of data. Alternative approaches based on widely available RNA-seq data are constrained because of sequence similarities between the transcriptomes of microbes/viruses and those of the host, compounded by the extreme abundance of host sequences in such libraries. Current approaches are also limited to specific microbial groups. There is a need for alternative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 92 publications
5
30
0
Order By: Relevance
“…A recently reported development is the use of longer probes: the electronic Tree of Life (eToL) method uses a net of much longer (64-mer) probes, prefiltered against human sequences, to identify (by homology; non-exact matches are detected) all non-human rRNA sequences in a given dataset. The method may be less prone to false positives because it refilters matches against human sequences and is relatively insensitive to single-nucleotide changes [54,55], and is being explored as a potential diagnostic method on patient samples.…”
Section: (V) Rna-seq With K-mer or Etol Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently reported development is the use of longer probes: the electronic Tree of Life (eToL) method uses a net of much longer (64-mer) probes, prefiltered against human sequences, to identify (by homology; non-exact matches are detected) all non-human rRNA sequences in a given dataset. The method may be less prone to false positives because it refilters matches against human sequences and is relatively insensitive to single-nucleotide changes [54,55], and is being explored as a potential diagnostic method on patient samples.…”
Section: (V) Rna-seq With K-mer or Etol Methodsmentioning
confidence: 99%
“…Over recent decades multiple studies on post-mortem AD brain have reported that diverse pathogens are present, ranging from bacteria to fungi to viruses [45][46][47][48][49][50][51][52][53]. Archaea, Chloroplastida, and Holozoa have also been reported in brain [54,55]. There are multiple potential routes of entry to the brain (Figure 2).…”
Section: Microbes In Ad Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of eTOL is especially important for viral sequences due to significant homology between human sequences. This can be combatted using a ‘stripping’ method where similar sequences are removed from the viral genome before characterization [ 67 ].…”
Section: The Human Microbiome Analysismentioning
confidence: 99%
“…We therefore developed a different approach that is both less resource-intensive and neutral with regard to the identity of the species detected. The electronic tree of life (eToL) method is based on a net of over 1000 64-mer probes designed from the 16S/18S rRNA sequences of all known branches of life, including archaea, bacteria, chloroplastida, amoeobozoa, basal eukaryota, fungi, and metazoa; the technical details of this method were reported previously (Hu et al 2022). We now apply this methodology to the study of the human brain microbiome in health and disease.…”
Section: Introductionmentioning
confidence: 99%